Dynamic coordination in RoboCup soccer simulation - Thien, Nguyen Duc; Duong, Nguyen Hoang; Hai, Pham Duc; Hung, Pham Ngoc; Huong, Do Mai; Hoa, Nguyen Ngoc; Hanh, Du Phuong (VNU Journal of Science: Natural Sciences and Technology; Vol 23 No 3, 2007)
Abstract